Otogen Tooth Transplantatıon And Orthodontıc Consıderatıons - Tülin Uğur Taner; Müge Pehlivanoğlu (Galenos Yayinevi, 2002)
Autotransplantation is a method of transplanting the impacted or erupted teeth from one site to another in the same individual in case of treating missing teeth. Autotransplantation can stimulate the alveolar growth, provide satisfactory solutions for aesthetic and occlusal problems and present an alternative approach for treating missing teeth in combination with the orthodontic treatment . The aim of this review is to evaluate all factors contributing to prognosis.